Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar IPS Siswa Kelas V di UPTD SD Negeri 125543 Pematangsiantar - Diana Galingging; Aprido.B. Simamora; Eva Pasaribu (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to see the influence of the Mind Mapping Learning Model on the Social Sciences Learning Outcomes of Class V Students at Uptd Sd Negeri 125543 Pematangsiantar. The population in this study were all students in class V UPTD SD Negeri 125543 Pematangsiantar with a total of 22 students. So the sample that will be used in this research is Nonprobability Sampling, and the entire population will be studied. Many students in research at UPTD SD Negeri 125543 Jl. Farel Pasaribu No. 76 totaling 22 people consisting of 8 men and 14 women. Based on the results of the data that researchers obtained with this research, it is to answer the problem formulation, namely "Is there an influence of the Mind Mapping learning model on the Social Sciences Learning Outcomes of class V students at UPTD SD Negeri 125543 Pematangsiantar. Thus, the alternative hypothesis in this research is accepted which states that there is an influence of the Mind Mapping learning model on the Social Studies Learning Outcomes of Class V Students at UPTD SD Negeri 125543 Pematangsiantar for the 2023/2024 Academic Year. This is proven by the t_count > t_table value using a significance level of 0.05 and df=21, namely 13,444 > 2.0738. This means that the learning model has an influence on learning outcomes in social studies lessons for class V students at UPTD SD Negeri 125543 Pematangsiantar. If the learning model is done well, it will greatly influence student learning outcomes in the classroom.